Opinion: redefining the role of the physician in laboratory medicine in the context of emerging technologies, personalised medicine and patient autonomy ('4P medicine'). Issue 3 (22nd December 2017) - Orth, Matthias; Averina, Maria; Chatzipanagiotou, Stylianos; Faure, Gilbert; Haushofer, Alexander; Kusec, Vesna; Machado, Augusto; Misbah, Siraj A; Oosterhuis, Wytze; Pulkki, Kari; Twomey, Patrick J; Wieland, Eberhard
Abstract : The role of clinical pathologists or laboratory-based physicians is being challenged on several fronts—exponential advances in technology, increasing patient autonomy exercised in the right to directly request tests and the use of non-medical specialists as substitutes. In response, clinical pathologists have focused their energies on the pre-analytical and postanalytical phases of Laboratory Medicine thus emphasising their essential role in individualised medical interpretation of complex laboratory results. Across the European Union, the role of medical doctors is enshrined in the Medical Act. This paper highlights the relevance of this act to patient welfare and the need to strengthen training programmes to prevent an erosion in the quality of Laboratory Medicine provided to patients and their physicians.